The Potential Regulatory Role of miR-378 in the Expression of Bone Morphogenetic Protein-15 in Infertile Women with Hyperprolactinemia (HPL) - Kamel, Maryam Dhary; Kandala , Nuha Joseph (Iraqi Journal of Science, 2023)
The aim of this study is to investigate the relationship between microRNA 378 and BMP15 gene expression levels in blood samples collected from 50 healthy fertile females as controls and 50 hyperprolactinemia infertile females by quantitative real-time polymerase chain reaction (RT-qPCR). Specific primers were designed for this purpose based on the sequences of microRNA 378 and BMP15 retrieved from NCBI and designed by primer 3 software. The result assessing the expression level of BMP15 in hyperprolactinemia (HPL) was 0.220, while the control group’s fold change value was 1.000. The HPL group showed downregulation in the expression of the BMP15 gene. While the fold expression values of the miRNA378 gene in the hyperprolactinemia (HPL) group were 2.227 and the control group’s mean value was 1.000, the HPL group showed up-regulation in the expression of the miRNA378 gene. The results of the study revealed that miR-378 has directly regulated BMP15 gene expression; based on this, BMP15 gene expression was obviously decreased. Therefore, the expression level of BMP15 was negatively correlated with miR-378 expression.